PH, KANDUNGAN BAHAN KERING DAN SIFAT FISIK SILASE LIMBAH KOL DENGAN BERBAGAI PENAMBAHAN LEVEL DEDAK PADI - Anwar Efendi Harahap; Muhammad Rusdi; Elfawati Elfawati (Jambura Journal of Animal Science, 2021)
Cabbage waste has the potential to be used as an alternative feed for livestock if the feed is processed sustainably. This study aims to analyze the determine the best level of use of rice bran in making cabbage waste silage seen from physical properties, pH and dry matter content of silage. This study used a completely randomized design  with 4 treatments and 4 replications. The treatments were A0 (cabbage waste 100%), A1 (cabbage waste 75% + rice bran 25%), A2 (cabbage waste 50% + rice bran 50%), A3 (cabbage waste 25% + rice bran 75%). The parameters measured include pH, odor, color, texture, presence of mushrooms and dry matter content. The results showed that the substitution of various levels of rice bran on cabbage waste had no significant effect (P 0.05) on the pH, color, texture and presence of mushrooms, had a significant effect (P 0.05) increased the aroma value, and had a very significant effect ( P 0.01) increased the dry matter content of the silage. The best treatment in this study is A3 (cabbage waste 25%, rice bran 75%) because it can increase the odor and dry matter content.